Measuring competitiveness of food processing industry in Malaysia - Ramzani, Sara Ravan; Ismail, Mohd Mansor; Abdurofi, Ilmas (Australian Academy of Business and Social Sciences, 2014)
This paper investigates the measuring competitiveness on the levels of competition for various productions of food products in Malaysia. The study is undertaken using the concept of comparative advantage. In the context of competitiveness of the Malaysian food processing industry the evaluation of comparative advantage has been undertaken. In order to penetrate a wider range of foreign markets, Malaysian food processors have to identify food sectors that are internationally competitive and could withstand internal and external shocks. The Malaysian competitiveness level was determined using the Domestic Resource Cost (DRC) and Social Cost Benefit (SCB) indicators. Twenty food sectors were assessed using the Malaysian food production and trade data from 2000 to 2008. The results indicate that in the post crisis period, Malaysia enjoys an above average level of comparative advantage in the production of twenty foods product in 2008. As expected, Malaysia has a comparative advantage in the food production.